Mapping literature of multicultural education: a bibliometric review - Roni Rodiyana; Bunyamin Maftuh; Sapriya Sapriya; Ernawulan Syaodih; Davi Sofyan; Khairul Hafezad Abdullah (International Journal of Evaluation and Research in Education (IJERE), 2024)
The value of multicultural education is acknowledged on a global scale, despite the fact that various barriers prevent its complete implementation. These include cultural, linguistic, religious, economic, difference in physical condition, and ethnic backgrounds. By assessing publishing trends, extracting data on author keyword trends, examining conceptual evolution, and establishing possible future research on this topic using the Scopus database. This study found that publications grew in quantity from 2013 to 2022, decreased in 2015 and 2018 but were not significant, and 2021 was the highest peak with 221 documents. With 111 publications, the United States is the most prolific and co-authored with authors from Canada, China, United Kingdom, Germany, Australia and South Korea. Based on thematic evolution, ‘subspace-clustering’, ‘conversational-system’, ‘aortic-aneurysm’, ‘Bayesian-network-classifier’, are themes or topics that have recently developed. By utilizing these important terms, the study of multicultural education can be examined more thoroughly and more extensive in the future in order to learn new knowledge. In conclusion, this research has the potential to contextualize previous research on the topic and create an evidence-based practice paradigm for future studies grounded in science.